Statistics from space: Next-generation agricultural production information for enhanced monitoring of food security in Mozambique. Component 4: Crop analytics for forecasting yields. - International Food Policy Research Institute (2023)
Seoul National University (SNU). 2023. Statistics from Space: Next-Generation Agricultural Production Information for Enhanced Monitoring of Food Security in Mozambique. Component 4. Crop analytics for forecasting yields. PowerPoint presentation given during the Project Inception Workshop, VIP Grand Hotel, Maputo, Mozambique, April 20, 2023